2017
DOI: 10.1016/j.ajpath.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Pyrophosphate Supplementation Prevents Chronic and Acute Calcification in ABCC6-Deficient Mice

Abstract: Soft tissue calcification occurs in several common acquired pathologies, such as diabetes and hypercholesterolemia, or can result from genetic disorders. ABCC6, a transmembrane transporter primarily expressed in liver and kidneys, initiates a molecular pathway inhibiting ectopic calcification. ABCC6 facilitates the cellular efflux of ATP, which is rapidly converted into pyrophosphate (PPi), a major calcification inhibitor. Heritable mutations in ABCC6 underlie the incurable calcification disorder pseudoxanthom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
98
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(107 citation statements)
references
References 58 publications
8
98
1
Order By: Relevance
“…Although intravenously administered, PPi had a half-life of only 42 min, administration of a single dose after the initial injury that initiates calcification halted subsequent calcification. Similar results were seen with etidronate, but not with alendronate [21■■]. This fascinating work suggests that even transiently elevated levels of circulating PPi may reverse BCP crystal deposition in some settings.…”
Section: Basic Calcium Phosphate-associated Arthritissupporting
confidence: 70%
See 1 more Smart Citation
“…Although intravenously administered, PPi had a half-life of only 42 min, administration of a single dose after the initial injury that initiates calcification halted subsequent calcification. Similar results were seen with etidronate, but not with alendronate [21■■]. This fascinating work suggests that even transiently elevated levels of circulating PPi may reverse BCP crystal deposition in some settings.…”
Section: Basic Calcium Phosphate-associated Arthritissupporting
confidence: 70%
“…The potential use of PPi as a therapeutic agent was recently highlighted [21■■]. For these studies, Pomozi et al used a mouse model of pathologic calcification based on mutations in ATP binding cassette subfamily C member 6 (ABCC6).…”
Section: Basic Calcium Phosphate-associated Arthritismentioning
confidence: 99%
“…The observed transient elevation found in healthy volunteers (Fig A) indicates that in both GACI and in PXE patients, PPi levels may be transiently raised to the physiological level when 67 or 98 mg Na 4 PPi/kg of body weight is taken. Importantly, it has been shown that inhibition of calcification in uremic rats and in PXE mice can be achieved by daily intraperitoneal injections of PPi triggering transient increase in plasma PPi levels (O'Neill et al , ; Pomozi et al , ). We determined a t 1/2 = 44.7 min what is rather similar to that published in rat (34.1 min; O'Neill et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Upstream of ENPP1, ABCC6-mediated ATP release from hepatocytes is the main source of circulating PPi (Jansen et al, 2014). The work by us and others suggests that reduced PPi levels is the major factor leading to ectopic mineralization in PXE, but there might be an alternative, as yet unknown mechanism, independent of PPi, by which ABCC6 prevents ectopic mineralization under physiologic conditions (Pomozi et al, 2017;Zhao et al, 2017). Recent observations suggest that ABCC6 is also involved in extracellular nucleotide metabolism, suggesting a central role for ABCC6 in purinergic signaling in the development of ectopic mineralization (Kauffenstein et al, 2018).…”
Section: Q LI Et Almentioning
confidence: 94%
“…After centrifugation, plasma was depleted of platelets by filtration through a Centrisart I 300-kDa mass cutoff filter (Sartorius, New York, NY) and stored at e80 C until further processing. PPi in plasma was measured by an enzymatic reaction using ATP sulfurylase to convert PPi into ATP in the presence of excess adenosine 5 0 -phosphosulfate (Sigma-Aldrich), a methodology adopted worldwide as described previously (Bauer et al, 2018;Dedinszki et al, 2017;Jansen et al, 2014;Li et al, 2017;Pomozi et al, 2017).…”
Section: Plasma Inorganic Pyrophosphate Assaymentioning
confidence: 99%